Awareness and Knowledge of Colorectal Cancer in Qassim Region, Saudi Arabia - AlSulaim, Lamees; AlOdhaybi, Ghadah; AlSalamah, Mona; AlHemedani, Munirah; AlMutairi, Ahad; AlKhamis, Raim; AlAyed, Ghadah (Asian Pacific Journal of Cancer Care, 2021)
Objective: Colorectal cancer (CRC) is a common and deadly disease. It is the third common malignancy in the world and the second leading cause of cancer-related deaths. Both environmental and genetic factors influence the risk of developing CRC. The clinical symptoms develop late in the course of the disease, and precursor lesions (adenomas) can be easily detected and removed. This study intends to evaluate the awareness of CRC in an Al-Qassim region and identify the (population) that can benefit from awareness and screening programs. Methods and Material: Quantitative observational, cross-sectional study using a self-administered electronic questionnaire survey was employed to include all males and females (Arabic speakers and older than 18) in the Al-Qassim region (March-June 2020). The questionnaire consisted of 13 multiple choice questions and two short answer questions in the Arabic language. The data were categorized according to gender, marital status, age, level of education, and residence to determine whether these demographic groups have a difference in Knowledge about CRC. Results: We used in the study an online distributed questionnaire, which was used before in another study. However, the assumed number needed for this study was 358; we collected 1430 responses (response rate is 400 %). In this study, the majority of the specimen was females 78 %, and 49.7 % had an age between 18 -32. the mean score of knowledge among the public in the Qassim region about CRC was 3.5573 ± 1.2664. the most symptoms related to CRC identified by the participants were blood in stool and abdominal pain, while the history of familiar CRC was the most known risk factors. The age, social status, and educational level had a significant correlation with the level of knowledge. Conclusions: Although older married individuals with higher education had more Knowledge of CRC than others, there were some misconceptions in the surveyed population regarding the function of the colon, how common the colon cancer and when they should be screened for colon cancer.